2018
DOI: 10.1186/s12879-018-3196-4
|View full text |Cite
|
Sign up to set email alerts
|

Is Xpert MTB/RIF appropriate for diagnosing tuberculous pleurisy with pleural fluid samples? A systematic review

Abstract: BackgroundTuberculous pleurisy (TP) presents a diagnostic problem due to the limitations of traditional diagnostic methods. Different studies with the Xpert MTB/RIF assay have drawn variable conclusions about its values in TP diagnosis. We conducted a meta-analysis to assess whether the Xpert MTB/RIF assay is appropriate for the diagnosis of TP using pleural fluid samples.MethodsA systematic search of four literature databases in English and Chinese language was performed to identify studies involving the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 38 publications
2
29
0
1
Order By: Relevance
“…Consistent with the literature (68-94%) [17], this research found that Xpert also showed high sensitivity (76.5%) in the diagnosis of EPTB. When pleural fluid was used to diagnose TP, the high specificity (100%) of Xpert suggested its high value in confirming TP diagnosis; however, the low sensitivity (15.0%), which was similar to previous studies (14-34%) [17,19,20], indicated that Xpert is of limited value for TP screening. Low sensitivity may be attributed to the presence of PCR inhibitors in pleural fluid [20], or the loading of MTB is too low that the detection limit cannot be reached even by centrifugation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with the literature (68-94%) [17], this research found that Xpert also showed high sensitivity (76.5%) in the diagnosis of EPTB. When pleural fluid was used to diagnose TP, the high specificity (100%) of Xpert suggested its high value in confirming TP diagnosis; however, the low sensitivity (15.0%), which was similar to previous studies (14-34%) [17,19,20], indicated that Xpert is of limited value for TP screening. Low sensitivity may be attributed to the presence of PCR inhibitors in pleural fluid [20], or the loading of MTB is too low that the detection limit cannot be reached even by centrifugation.…”
Section: Discussionsupporting
confidence: 79%
“…When pleural fluid was used to diagnose TP, the high specificity (100%) of Xpert suggested its high value in confirming TP diagnosis; however, the low sensitivity (15.0%), which was similar to previous studies (14-34%) [17,19,20], indicated that Xpert is of limited value for TP screening. Low sensitivity may be attributed to the presence of PCR inhibitors in pleural fluid [20], or the loading of MTB is too low that the detection limit cannot be reached even by centrifugation. Thus, this study together with previous literature, did not recommend the use of pleural fluid as a specimen of Xpert for the diagnosis of TP, until pleural fluid was optimized for improved sensitivity.…”
Section: Discussionsupporting
confidence: 79%
“…and 51% [10][11][12]. Other studies showed that pleural biopsies taken by medical thoracoscopy were the best specimens for diagnosing TPE [9,13,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, WHO expanded its application for the diagnosis of extrapulmonary tuberculosis in adults and children, although the samples were only restricted to cerebrospinal fluid, lymph node fluid, and tissue specimens [9]. The pooled sensitivity of Xpert in the diagnosis of tuberculous pleural effusion (TPE) was between 30% and 51% [10][11][12]. Studies have shown that pleural biopsies taken under medical thoracoscopy are better specimens for diagnosing tuberculous pleuritis compared to pleural fluid [9,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…(23) tarafından 23 çalışma dâhil edilerek plevral sıvı örneklerinde GX testinin uygunluğunun değerlendirildiği bir meta-analizde; testin duyarlılığı %30 olarak çalışmamıza benzer şekilde düşük bulunmuştur. Aynı meta-analizde; GX testinin plevral sıvı örneklerinde düşük duyarlılığının PCR inhibisyonu ve uygunsuz veya yetersiz örnekleme yöntemlerinden kaynaklanabileceği belirtilmiş, testin TB tanısını dışlamada değerinin düşük olduğundan sözsedilmiştir (23) . Mazzola ve ark.…”
Section: Mgit Sire Yöntemiunclassified